Growth of Grapevine Rootlings in Soil from a Field Nursery Naturally Infested with Meloidogyne incognita and Rhizoctonia solani - Walker, G.E. (South African Journal of Enology and Viticulture, 2017)
Grapevine rootlings (V. vinifera cv. Colombard and V. champini cv. Ramsey) were grown in pots containing soil from a field nursery naturally infested with Meloidogyne incognita and Rhizoctonia solani. Vine growth in untreated soil with or without dilution using clean sand was compared with growth in soil subjected to a range of treatments including: disinfestation either by aerated steaming or by fumigation with methyl bromide, amendment with 1 % (w/w) corn-meal, or treatment with fungicides and/or fenamiphos. Vines grown in infested soil suffered root rot caused by R. soiani and galling caused by M. i11cog11ita. Both disinfestation treatments effectively prevented root rotting and galling, and increased the growth of Colombard but not Ramsey. Fenamiphos increased the growth of the nematode-susceptible Colombard but not Ramsey at a low initial population density of three juveniles per 200 g of soil. Nematode reproduction on Ramsey in the shadehouse and in the field nursery on other rootstocks regarded as being highly resistant to root-knot nematode was higher than previously reported with other South Australian Meloidogyne spp. populations. Soil dilution increased Colombard growth and amendment with corn-meal reduced nematode reproduction on both cultivars. Rhizoctonia solani caused root rot in both cultivars but quintozene and tolclofos-methyl increased root growth only of Ramsey. These fungicides and pencycuron reduced the severity of root rot; tolclofos-methyl was particularly effective in reducing the frequency of isolation of R. solani from roots. Potassium phosphite did not reduce root rot or increase root growth. Quintozene, tolclofos-methyl and pencycuron also inhibited nematode reproduction but these effects were not consistently observed in both cultivars. Most isolates of R. solani from grapevine roots belonged to anastomosis group 4. Field observations suggested that galled roots were more prone to infection by R. solani than ungalled roots.